2015
DOI: 10.1038/ni.3099
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 signaling modulates activation of STAT transcription factors to antagonize retinoic acid signaling and control the TH17 cell–iTreg cell balance

Abstract: Interleukin 17 (IL-17)-producing helper (TH17) and inducible regulatory CD4+ T (iTreg) cells emerge from an overlapping developmental program. In the intestines, the vitamin A metabolite retinoic acid (RA) is produced at steady state and acts as an important cofactor to induce iTreg cell development while potently inhibiting TH17 development. Here, we found that IL-1 was required to fully override RA-mediated Foxp3 expression and induce protective TH17 responses. Through induction of an NF-κB-dependent repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 47 publications
7
135
0
Order By: Relevance
“…Experiments have shown that the addition of IL-1b to Tregs results in the loss of Treg cellular identity and differentiation into IL-17-producing TH17 cells. One possible mechanism may be the effects of IL-1b on the production of retinoic acid, a key signaling molecule that can modulate Treg development through the Stat3 pathway [86]. In contrast to the effects of IL-1b on Treg differentiation, a new study has identified IL-33 to have a positive role in the differentiation and maintenance of Tregs.…”
Section: Crosstalk and Synergy Between Il-18 And Il-22 In Mucosal Infmentioning
confidence: 98%
“…Experiments have shown that the addition of IL-1b to Tregs results in the loss of Treg cellular identity and differentiation into IL-17-producing TH17 cells. One possible mechanism may be the effects of IL-1b on the production of retinoic acid, a key signaling molecule that can modulate Treg development through the Stat3 pathway [86]. In contrast to the effects of IL-1b on Treg differentiation, a new study has identified IL-33 to have a positive role in the differentiation and maintenance of Tregs.…”
Section: Crosstalk and Synergy Between Il-18 And Il-22 In Mucosal Infmentioning
confidence: 98%
“…It has been reported that IRAK1 directly phosphorylates STAT3 in T cells cultured with TGF-b and IL-6 (16), yet we found that in the presence of IL-23, IRAK1 signaling acts downstream of IL-1b to promote sustained IL-17 production. It was shown recently that IL-1 additionally promotes STAT3 tyrosine phosphorylation induced by IL-23 by repressing suppressor of cytokine signaling 3, a negative regulator of the STAT3 pathway (22). In line with our finding that IRAK1 signaling is not required for upregulation of RORgt expression by IL-1b, it was shown that lack of MyD88 in CD4 + T cells impairs Th17 cell generation without affecting RORgt expression (23 the MyD88-mediated activation of the mTOR signaling pathway by IL-1b promotes IL-23R induction and sustains IL-17 production.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in neonates who became asthmatic by age 9, SMAD3 promoter hypermethylation, an epigenetic configuration consistent with low SMAD3 expression, was strongly associated with high IL-1β production. This convergence may destabilize the T regulatory cell program, enhance inflammation, and promote Th17 differentiation [27], ultimately favoring the development of asthma. While it is unclear whether these mechanisms operate pre-and/or perinatally, detection of the relationship between SMAD3 methylation and IL-1β production selectively among children of asthmatic mothers implies that the in utero environment is critical for directing the epigenetic trajectory towards childhood asthma.…”
Section: The Epigenetic Trajectory To Asthma Begins At Birth (If Not mentioning
confidence: 99%